2022
DOI: 10.1155/2022/4852201
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the Effects of Intramedullary Nailing and Plate Fixation on Lower-Extremity Deep Vein Thrombosis after Tibial Fractures

Abstract: Lower-extremity deep vein thrombosis (DVT) is prone to occur after internal fixation of tibial fractures. This study analyzed the effect of intramedullary nailing (IMN) and plate fixation (PF) on lower-extremity DVT, providing reliable reference and guidance for future clinical treatment of tibial fractures. Sixty-eight patients with tibial fractures admitted to Honghui Hospital, Xi’an Jiaotong University, between February 2019 and October 2020 were selected as research participants, of which 32 cases treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%